Din Mehmeti, prominent poet of Kosovo - Muhadri, Besim (Technium Social Sciences Journal, 2023)
Din Mehmeti is a prominent poet of Albanian poetry in Kosovo. For 60 years of his literary creativity, he has published 17 books of poetry, books which have been appreciated by both readers and literary critics. It has also been translated into several languages of the world, such as English, Italian, French, Croatian, etc. It is distinguished for its high artistic sensitivity and for a rich artistic representation. One of his main preoccupations remains the fate of his people and the freedom of Kosovo. The purpose of our work is to present the stages of his poetic development but also other aspects related to the literature of this poet.